Clojure data analysis cookbook : dive into data analysis with Clojure through over 100 practical recipes for every stage of the analysis and collection process - Rochester, Eric (Packt Publishing, 2015)
This book is for those with a basic knowledge of Clojure, who are looking to push the language to excel with data analysis.